Innovation in sugarcane bagasse briquettes for community empowerment: Inovasi briket limbah tebu untuk pemberdayaan masyarakat - Muhammad Zamroni; Abdurohim; Helena Pangastuti; Yufi Nafi’atuzahro; Veny Alifia Febrianti; Annisa Rofiffah Rochma; Meytri Kurniasih; Manie Sari Ama Putri; Freintia Herli Yanti; Sakinah Audria Mayangsari; Chelsea Aulia Arifan; Surya Kusuma Wardhana (KHD Production, 2026)
Sugarcane is a major agricultural commodity cultivated by rural communities; however, sugarcane bagasse and leaves generated during harvesting are often underutilized and commonly burned, contributing to environmental pollution. Limited community knowledge and skills in waste management remain key challenges. This community service program aimed to enhance community capacity in processing sugarcane waste into value-added briquettes as an alternative and environmentally friendly fuel source. The program employed a participatory and educational approach consisting of three stages: preparation, implementation, and evaluation. Activities included socialization, hands-on training, and continuous assistance in briquette production techniques. The results demonstrated increased community awareness and improved skills in managing agricultural waste productively. The program contributed to reducing open burning practices and creating potential small-scale business opportunities. The produced briquettes exhibited favorable characteristics, including longer burning duration and lower smoke emissions. This initiative supports environmental sustainability while promoting local economic development through the utilization of agricultural waste.